2019
DOI: 10.1007/s00420-019-01420-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and sickness absence: a prospective study of 17,795 employees in Denmark

Abstract: Objectives The aims were to examine (1) the prospective association between perceived stress and sickness absence, and if this association (2) differed by sex, and (3) was stronger when only long-term sickness absence (≥ 31 days) instead of all-length sickness absence (≥ 1 day) was included. Moreover, different cut-points for the length of the sickness absence periods were applied. Methods We followed respondents (10,634 women and 7161 men) from the ‘Work Environment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 36 publications
1
42
1
Order By: Relevance
“…of all Danes from 2008 until 2018; (2) the education register, containing dates of the highest education level completion for all Danes; (3) the death register, with death dates for all deceased Danes; (4) the emigration and immigration register, containing dates on all emigrations and immigrations in Denmark; (5) the Register of Work Absences (RoWA), containing registrations of employment-related sickness absences down to one day of duration. The RoWA cover all public employees and a yearly weighted sample from the private sector with a coverage of approximately 37% of all private employees [17]; and (6) the employment register, containing dates on employment periods for the individuals in the RoWA register. It is important to note that in the multi-state model an individual is categorized as sick-listed, only when the sickness absence refers to the health of the individual.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…of all Danes from 2008 until 2018; (2) the education register, containing dates of the highest education level completion for all Danes; (3) the death register, with death dates for all deceased Danes; (4) the emigration and immigration register, containing dates on all emigrations and immigrations in Denmark; (5) the Register of Work Absences (RoWA), containing registrations of employment-related sickness absences down to one day of duration. The RoWA cover all public employees and a yearly weighted sample from the private sector with a coverage of approximately 37% of all private employees [17]; and (6) the employment register, containing dates on employment periods for the individuals in the RoWA register. It is important to note that in the multi-state model an individual is categorized as sick-listed, only when the sickness absence refers to the health of the individual.…”
Section: Methodsmentioning
confidence: 99%
“…Perceived stress, defined as the degree to which situations in one’s life are appraised as stressful [ 12 ], is associated with an increased risk of sickness absence and early retirement [ 13 , 14 , 15 , 16 , 17 ]. A recent large national Danish study showed that the prevalence of perceived stress is particularly high among working adults aged 18–44 years, with a prevalence of 35% and 24% for women and men, respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 23 Perceived stress has recently been found to be associated with risk of absence due to sickness, suggesting that reduced stress among surgical personnel might have a positive effect on absence over time. 28 In our study, the non-sterile nurses experienced an improvement to their working environments following the implementation and use of the IOR.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, work stressors specific to the job of nurses are seldom assessed for their associations with unplanned absenteeism. A study on the association of job stress and sickness absence among the general working population in Denmark found that female workers had different strength of association for perceived stress between long-term sickness absence and all-length sickness absence [ 22 ]. Thus, to study the association of work stress and unplanned absenteeism among nurses, of whom the majority are female, the duration of MC or EL needs to be analyzed too.…”
Section: Introductionmentioning
confidence: 99%